2019
DOI: 10.1038/s41598-019-46775-8
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-borne miR-216b modulates cell proliferation during early embryo development via K-RAS

Abstract: Semen fertilizing potential is dependent upon the morphological, functional and molecular attributes of sperm. Sperm microRNAs (miRNAs) were recently shown to hold promise regarding their association with different fertility phenotypes. However, their role in fertility regulation remains to be determined. We postulated that sperm miRNAs might regulate early embryonic development. From this perspective, sperm quality and 380 sperm miRNAs were investigated in frozen–thawed semen from high (HF; 54.3 ± 1.0% pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 51 publications
(69 reference statements)
1
29
0
Order By: Relevance
“…In cattle, different studies reported miRNA profile alteration associated with different sperm quality levels and fertility phenotypes. A previous study by qPCR miRNA profiling with a customized panel of bovine-specific miRNAs reported several miRNAs altered in HF and LF bulls isolated directly from cryopreserved semen ( 1 , 10 ) or after purification with Percoll separation ( 8 ). Small-RNA sequencing of high and low motile fractions isolated from cryopreserved sperm using Percoll gradient, together showed variation of quality parameters and significant changes in miRNA expression ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cattle, different studies reported miRNA profile alteration associated with different sperm quality levels and fertility phenotypes. A previous study by qPCR miRNA profiling with a customized panel of bovine-specific miRNAs reported several miRNAs altered in HF and LF bulls isolated directly from cryopreserved semen ( 1 , 10 ) or after purification with Percoll separation ( 8 ). Small-RNA sequencing of high and low motile fractions isolated from cryopreserved sperm using Percoll gradient, together showed variation of quality parameters and significant changes in miRNA expression ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mature spermatozoa contain coding and non-coding RNAs, some of which are involved in the regulation of many physiological pathways related to spermatogenesis, sperm maturation, and early embryonic development with the potential to modulate sperm morpho-functional features as well as male reproductive ability ( 8 ). Among small RNA species, miRNAs are associated with sperm cell fertility status and embryo development ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm-borne miR−449b overexpression in cloned embryos is associated with enhanced cleavage rates at the 8-cell stage and lower rates of apoptosis in the blastocyst (Wang et al, 2017). Sperm-borne miR−216b was recently shown to be present at higher abundance in spermatozoa from low fertility bulls and is associated with a reduced first cleavage rate as well as a reduced number of cells in blastocysts (Alves et al, 2019). In parallel, the RNAs that are acquired by spermatozoa during epididymal transit were shown to be essential for embryo implantation and development in mice (Conine et al, 2018(Conine et al, , 2019.…”
Section: Sperm Mirnasmentioning
confidence: 99%
“…Within livestock animals, bulls that presented satisfactory sperm quality and history of distinct fertility (high vs. low fertility) displayed different profiles of sperm miRNAs that are summarized in Table 2 (Fagerlind et al, 2015;Alves et al, 2019;Menezes et al, 2019). Similarly, spermatozoa from boar featuring low motility and a high percentage of abnormalities, displayed a higher abundance of the miRNAs: let−7a, let−7d, let−7e, and miR−22; and lower abundance of miR−15b (Curry et al, 2011) compared with spermatozoa presenting with normal features.…”
Section: Linking Mirnas To Male (In)fertility Statusmentioning
confidence: 99%